2021
DOI: 10.1186/s13104-021-05505-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of Helicobacter pylori from biopsies of patients in Lagos, Nigeria using real-time PCR—a pilot study

Abstract: Objective Prompt diagnosis of Helicobacter pylori infection is essential for proper treatment and eradication of the pathogen because prolonged infection could lead to gastric cancer. Sensitive and cost effective diagnostic methods are key to guiding treatment options that will reduce mortality. This study was aimed at detecting H. pylori from biopsies of peptic ulcer patients. Real-time PCR using TaqMan and EvaGreen assays targeting 16S rRNA and ureA genes were used to detect H. pylori DNA ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Results revealed that PCR using the glmM gene was also a reliable test compared to histology and the CLO test. Other studies Smith et al [103], Onyekere et al [77], Smith et al [78], Palamides et al [16], and Ajayi et al [79] used SAT, UBT, stool-PCR, UBT and culture from biopsy, and qPCR, respectively, in the diagnosis of HPI in Nigeria. The use of endoscopy, histology, and culture in the diagnosis of HPI has also been reported in Senegal by Breurec et al [80]; Seck et al [81]; and Doh et al [82].…”
Section: Diagnosis Of Hpi In Africamentioning
confidence: 99%
“…Results revealed that PCR using the glmM gene was also a reliable test compared to histology and the CLO test. Other studies Smith et al [103], Onyekere et al [77], Smith et al [78], Palamides et al [16], and Ajayi et al [79] used SAT, UBT, stool-PCR, UBT and culture from biopsy, and qPCR, respectively, in the diagnosis of HPI in Nigeria. The use of endoscopy, histology, and culture in the diagnosis of HPI has also been reported in Senegal by Breurec et al [80]; Seck et al [81]; and Doh et al [82].…”
Section: Diagnosis Of Hpi In Africamentioning
confidence: 99%
“…Limitations include costs and time constraints but microbial culture also enables phenotypical antimicrobial susceptibility testing (AST) 180 . Molecular testing from formalin-embedded biopsy or RUT samples with PCR methods, of which quantitative PCR is most appropriate, and fluorescence in situ hybridization is highly accurate in the detection of H. pylori 185 and can also be combined with molecular resistance testing 186 .…”
Section: Primermentioning
confidence: 99%
“…Stool PCR and direct detection of H. pylori in biopsies using real-time PCR have been demonstrated in Nigeria [96]. Droplet digital PCR (ddPCR) is more sensitive than other PCR methods.…”
Section: Wg 1: Epidemiologymentioning
confidence: 99%